Thermal, mechanical, and transport properties of C-S-H at the molecular scale: A force field benchmark - Tulio Honorio; Fatima Masara; Gang Huang; Farid Benboudjema (Cement)
Interlayer species play a critical role in the thermo-hydro-mechanical properties of C-S-H at the molecular scale. We investigate how different choices in molecular modeling of C-S-H impact the behavior of interlayer species and subsequently affect the thermal, mechanical, and transport properties. By comparing various force fields, we identify the most effective approach per property. The choice of water force field has minimal influence on properties. As for heat capacity, we show that accounting for quantum corrections is important in calculating the thermal conductivity of C-S-H. Different choices of force fields lead to better agreement of estimates of the heat capacity, thermal conductivity, and thermal expansion of C-S-H with available experimental data. Non-reactive and reactive force fields exhibit similar behavior in tensile and shear tests. ClayFF Ca(aq) leads to a reduced interlayer diffusion coefficient. This research underscores the imperative role of accurately characterizing interlayer species in understanding C-S-H behavior.